Total Suspended Solid Concentration Dynamics and Distribution Based on Geospatial Models in Mojo River Estuary, Pemalang - Aini, Firly Nur; Indarjo, Agus; Zainuri, Muhammad; Endrawati, Hadi; Redjeki, Sri; Pribadi, Rudhi; Setiyono, Heryoso; Suryoputro, Agus Anugroho Dwi (Buletin Oseanografi Marina, 2024)
Total suspended solids (TSS) concentrations and distribution provide information to determine the quality of the carrying capacity of waters as marine resources. The purpose of the research is to analyze the concentration and distribution of TSS in marine waters due to anthropogenic impacts on land. The concentration and distribution changes of TSS were analyzed using a geospatial model approach. The in-situ data were collected in September 2023 at 14 stations in the east monsoon and analyzed in the laboratory using the gravimetric method. The results show that TSS concentration range from 29.2–52.6 mg/L. The distribution of MPT content in the Mojo River Estuary, Pemalang has several groups of stations with convergent forms, where the high source of MPT comes from around the lagoon, namely the aquaculture and mangrove areas, then in general it is also affected by waste from anthropogenic activities of the, surrounding industries seasonal currents, which are related to wind and seasons, as well as currents due to waters from tides.